Analisis Mekanisme Produk Tabungan Emas Sebagai Perlindungan Nilai Aset Nasabah di Pegadaian Syariah Lumajang (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
Gold is one of the investment instruments that is quite safe from ancient times to the present, gold has intrinsic value so that its value is not affected by inflation from year to year. In Islam, gold is one of the assets that are recommended to be owned by every individual, as the words of the Prophet Muhammad SAW: "There will come to humans, a time when nothing is useful at that time except Dinar and Dirham" (HR. Ahmad from Miqdam bin Madikarib). This study aims to discuss the mechanism of using Gold Savings Products at Pegadaian Syariah Lumajang and to measure the statistics of gold prices in one year. This study uses a qualitative approach with a case study type. The results show that the Gold Savings product has the advantage of being easy to access, making it easier for people to have Gold savings, and in practice has two Akad in its transactions which of course do not violate Islamic law. Savings products are different from Gold Installments because they are not tied to Installments. Gold prices have shown an increase in the past year so that they have the potential to maintain asset values ​​so that they are not affected by inflation.